Advanced antifouling and antibacterial hydrogels enabled by controlled thermo-responses of a biocompatible polymer composite. (11th October 2022) - Pan, Fei; Zhang, Sixuan; Altenried, Stefanie; Zuber, Flavia; Chen, Qian; Ren, Qun
Abstract : To optimally apply antibiotics and antimicrobials, smart wound dressing conferring controlled drug release and preventing adhesions of biological objects is advantageous. Abstract : To optimally apply antibiotics and antimicrobials, smart wound dressing conferring controlled drug release and preventing adhesions of biological objects is advantageous. Poly( N -isopropylacrylamide) (PNIPAAm), a conventional thermo-responsive polymer, and poly(2-methacryloyloxyethyl phosphorylcholine) (PMPC), a typical antifouling polymer, have therefore potential to be fabricated as copolymers to achieve dual functions of thermo-responsiveness and antifouling. Herein, a hydrogel made of PNIPAM– co -PMPC was designed and loaded with octenidine, a widely applied antimicrobial agent for wound treatment, to achieve both antifouling and triggered drug release. The thermo-switch of the fabricated hydrogel allowed 25-fold more octenidine release at 37 °C (infected wound temperature) than at 30 °C (normal skin temperature) after 120 minutes, which led to at least a 3 lg reduction of the viable bacteria at 37 °C on artificially infected wounds. Furthermore, we pioneeringly assessed the antifouling property of the material in PBS buffer using single molecule/cell/bacterial force spectroscopy, and revealed that the fabricated hydrogel displayed distinctive antifouling properties against proteins, mammalian cells, and bacteria. This work demonstrated a promising design of a hydrogel applicable for preventing and treating wound infections. The concept of dual-functional materials can be envisaged for other clinical applications related to the prevention of biofilm-associated infections, such as urinary catheters, stents, and dental implants.